2011
DOI: 10.1002/jms.1899
|View full text |Cite
|
Sign up to set email alerts
|

An LC–MS screening method with library identification for the detection of steroidsin dietary supplements

Abstract: For many years anabolic-androgenic steroids (AAS) are by far the most frequently detected pharmacological substances in doping control. In order to improve their performances, professional sportsmen are often tempted to take dietary supplements. However, due to the frequent and widespread occurrence of contaminated supplements, the use of such products is not without risk for the athletes involved. In order to minimize the chances of an unattended positive doping test or serious health problems, fast and relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…The analysis of food supplements requires sample pretreatment in order to have them in the right physical state for analysis, to reduce interferences present in the matrix and to detect low concentrations of analytes. The techniques used till now for these purposes involved a dissolution in a solvent (Van Poucke et al 2007;Doué et al 2014;Krug et al 2014) followed sometimes by liquidliquid extraction (LLE) Baume et al 2006;Martello et al 2007;Strano-Rossi et al Forthcoming), otherwise by SPE (Becue et al 2011) or a filtration (Cho et al 2014). The subsequent detection step of AASs is mostly performed by GC-MS (Kamber et al 2001;Delbeke et al 2002;Geyer et al 2004;Baume et al *Corresponding author.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…The analysis of food supplements requires sample pretreatment in order to have them in the right physical state for analysis, to reduce interferences present in the matrix and to detect low concentrations of analytes. The techniques used till now for these purposes involved a dissolution in a solvent (Van Poucke et al 2007;Doué et al 2014;Krug et al 2014) followed sometimes by liquidliquid extraction (LLE) Baume et al 2006;Martello et al 2007;Strano-Rossi et al Forthcoming), otherwise by SPE (Becue et al 2011) or a filtration (Cho et al 2014). The subsequent detection step of AASs is mostly performed by GC-MS (Kamber et al 2001;Delbeke et al 2002;Geyer et al 2004;Baume et al *Corresponding author.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…Different studies recently available in the literature have shown the presence of anabolic steroids and designer drugs in dietary supplements, such as androstenedione, 5‐androsten‐3β‐ol‐17‐one (dehydroepiandrosterone; DHEA), methandienone, testosterone esters, androst‐4‐ene‐3β‐17β‐diol, boldenone, among others (Geyer and others ; Becue and others ; Aqai and others ; Odoardi and others ). Table shows a compilation of studies reporting the presence of illegal substances in dietary supplements.…”
Section: Pfs Often Adulteratedmentioning
confidence: 99%
“…Additionally, the use of optimized sample extraction and clean‐up protocols has been suggested by different authors, including the use of liquid‐liquid extraction (Geyer and others ; Schramek and others ; Strano‐Rossi and others ), solid‐phase extraction (SPE) (Stepan and others ; Peters and others ; Becue and others ), and QuEChERS (quick, easy, cheap, effective, rugged, and safe) procedure (Vaclavik and others ). When analyzing 88 steroid compounds in PFS using ultra‐performance liquid chromatography‐MS (UPLC‐MS), Becue and others () concluded that a clean‐up procedure using a SPE NH 2 ‐column was necessary for improved sensitivity and selectivity, since it allowed for a substantial reduction of background noise by retention of polar matrix effects. Stepan and others () employed dispersive SPE using primary secondary amine (PSA) as a sorbent to effectively remove polar components such as sugars, 4‐hydroxy‐2‐methoxycinnamaldehyde and partially remove fatty acids and vanillin.…”
Section: Determination Of Adulterating Substancesmentioning
confidence: 99%
“…The increasing distribution and misuse of black market products urgently requires comprehensive analytical procedures for their identification. Several analytical methods published in recent years have focused on the analysis of counterfeit AAS products primarily using liquid chromatography (LC) and gas chromatography (GC), often coupled with mass spectrometry (MS) . Although studies have focused on testing the quality of AAS products, quantitative analysis is necessary to avoid underestimating the counterfeit rate of AAS products .…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods published in recent years have focused on the analysis of counterfeit AAS products primarily using liquid chromatography (LC) and gas chromatography (GC), often coupled with mass spectrometry (MS). 3,[11][12][13][14][15][16] Although studies have focused on testing the quality of AAS products, 16,17 quantitative analysis is necessary to avoid underestimating the counterfeit rate of AAS products. 10 different dietary supplements and concluded that 60% of the samples contained at least one AAS.…”
Section: Introductionmentioning
confidence: 99%